Chronic Obstructive Pulmonary Disease – Recent Updates - Chakrabortty, Rajashish (Bangladesh Journal of Medicine, 2023)
Chronic Obstructive Pulmonary Disease (COPD) is one of the leading causes of death and disability globally as well as in Bangladesh. Continuing research is essential to combat the threat posed by rising prevalence of COPD. Here we present recent updates in the field of COPD research. The revised definition of COPD emphasizes COPD as a heterogeneous disease affecting the bronchi, bronchioles, alveoli and pulmonary vasculature. The traditional view of COPD as a smoker’s disease with a late onset has been replaced by the new concept of COPD etiotypes, which recognizes the contribution of developmental, genetic, environmental, infective and idiopathic contributions to COPD. Vaping has also been proposed as a risk factor for COPD. Two precursors to COPD – pre-COPD and PRISm – have also been proposed to highlight the opportunity of early detection and management. Clinical classification of COPD has been updated to the simplified ABE approach. New recommendations for treatment prioritize the initial use of a fixed dose LABA+LAMA combination. A more judicious use of ICS in COPD patients is recommended, in those with specific indications (exacerbation-prone, high eosinophil counts, or concomitant asthma). In this population, single-inhaler triple-therapy of LABALAMA- ICS has replaced previous recommendations of LABA-ICS. A strong emphasis has been placed on appropriate, individualized choice of inhaler device and training on technique for each patient. Interventional pulmonology and minimally invasive surgery also have a growing role in management of selected patients. Small airways disease is a key cause of morbidity in COPD. Newer diagnostic techniques, such as impulse oscillometry, and novel drug formulations (extra-fine particles, cosuspension forms, soft mist inhalers) are under study. The monoclonal antibody dupilumab has also shown promise in reducing COPD exacerbation. Finally, COPD is a multisystem disease and any management plan must include steps to identify and treat associated co-morbidities. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 197